Genetic variation of pantropical Terminalia catappa plants with sea‐drifted seeds in the Bonin Islands: suggestions for transplantation guidelines. Issue 1 (14th January 2016) - Setsuko, Suzuki; Ohtani, Masato; Sugai, Kyoko; Nagamitsu, Teruyoshi; Kato, Hidetoshi; Yoshimaru, Hiroshi
Abstract: The Bonin Islands are endowed with endemic species. However, these species are at risk of extinction because of the exuberance of invasive alien plants. Therefore, native plant species should be revegetated after eradicating alien plants. We investigated the genetic variation of T erminalia catappa populations in the Bonin Islands by using nuclear (n) microsatellites (simple sequence repeats [SSRs]) and chloroplast (cp) DNA. No significant differences were observed in the genetic diversity of nSSRs among 22 populations. However, recent bottlenecks were detected in three populations on the Chichijima Island group. nSSR variation and cpDNA haplotypes suggested the presence of two genetically distinct groups in the Mukojima and Chichijima Island groups and the Hahajima Island group. A similar genetic structure was observed in plants and animals in the Bonin Islands. Populations on the three islands, which were separated from other islands in each island group when the water depth was 50‐m lower than the present level, were dominated by unique nSSRs clusters, suggesting that historical changes in island connections during the Pleistocene era affected genetic substructuring. These results suggested that different factors contributed to the genetic structure of T . catappa on different geographic scales. At the whole‐island level, the genetic structure was determined by long‐distance seed dispersal by ocean currents. At the island‐group level, the genetic structure was determined by historical changes in island connections caused by changes in the sea level due to glacial–interglacial transition. These findings would help in establishing transplantation zone borders for revegetating T . catappa on the Bonin Islands. Abstract : At the whole‐island level, the genetic structure of Terminalia catappa was determined by long‐distance seed dispersal by ocean currents. At the island‐group level, the genetic structure was determined by historical changes in island connections caused by changes in the sea level due to glacial–interglacial transition.